Diagnostic patterns and predictors of cognitive outcomes in autistic children in Singapore - Chui Mae Wong; Hwan Cui Koh; Pratibha Agarwal; Lourdes Mary Daniel (Annals, Academy of Medicine, Singapore)
Introduction: This study aimed to examine patterns of diagnosis, cognitive and adaptive functioning, and school placement outcomes in autistic children in Singapore, and to assess earlier predictive factors of cognitive outcomes. Method: Retrospective data were extracted from medical records of a specialist developmental paediatrics service for children born in 2008–2011 and referred to the autism clinic or were given a diagnosis of autism. Data items included demographic data, diagnostic methods, psychological assessment results, early intervention attendance and school placement outcomes. Results: A total of 2124 children (82.6% male; 66.4% Chinese, 13.4% Malay, 9.8% Indian and 10.5% Others) were diagnosed with autism from the 4 birth-year cohorts. The mean (SD) age of the first clinical diagnosis of autism was 3.56 (1.14) years, with 81.0% of children receiving a concordant initial clinical diagnosis. A total of 1811 (85.2%) had a formal diagnostic assessment using the Autism Diagnostic Observation Schedule (ADOS) at a mean (SD) age of 4.16 (1.11) years. Of 1326 with cognitive and adaptive assessment results, 16.6% had mild and 19.8% had moderate-severe cognitive impairment. Of 1483 with school placement outcomes, 45.9% went to mainstream schools, 21.8% entered SPED schools offering the national curriculum and 32.3% required customised curriculum SPED schools. Logistic regression showed that factors predicting intellectual impairment included higher ADOS scores (aOR 95% CI 1.13 [1.08–1.19] for Comm+SI total and 1.53 [1.33–1.75] for SBRI total), higher social communication level of support (based on the DSM-5 criteria) (aOR [95% CI] 2.14 [1.10–4.16] for level 2 and 14.94 [5.77–38.64] for level 3), and minority race (aOR [95% CI] 2.82 [1.52–5.20] for Malay, 5.19 [2.36–11.44] for Indian, and 4.54 [1.91–10.79] for Others). Conclusion: These findings could guide policymakers and practitioners worldwide to strategically allocate diagnostic, intervention and educational resources, maximising developmental outcomes for autistic children across diverse settings.